Project-based learning with cisco packet tracer: effects on students’ cognitive domain learning outcomes and critical thinking abillity - Dafina Nur Faiza Iza; Mohammad Wildan Habibi Wildan (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This study aims to analyze the effect of Project-Based Learning (PjBL) supported by Cisco Packet Tracer on students’ cognitive domain learning outcomes and Critical Thinking Ability (CTA) regarding Local Area Network (LAN) installation. This study employed a quasi-experimental method with a pretest-posttest control group design. The research sample consisted of 120 11th-grade Computer and Network Engineering (CNE) students at SMKN 1 and SMKN 2 Kediri, divided into an experimental group and a control group. The research instruments included 13 multiple-choice questions to measure cognitive learning outcomes and 5 essay questions to measure CTA. Data were analyzed using the independent samples t-test and the paired samples t-test. The results showed that the mean posttest score for cognitive learning outcomes in the experimental group was higher than that in the control group, with scores of 8.42 and 7.40, respectively (p=0.036). The experimental group also demonstrated higher CTA, with scores of 15.08 and 13.77 in the experimental and control groups, respectively (p=0.024). These findings indicate that PjBL assisted by Cisco Packet Tracer is effective in improving students’ cognitive learning outcomes and CTA.